Hla‐C genetic diversity and evolutionary insights in two samples from Brazil and Benin. (24th August 2020) - Souza, Andreia S.; Sonon, Paulin; Paz, Michelle A.; Tokplonou, Léonidas; Lima, Thálitta H. A.; Porto, Iane O. P.; Andrade, Heloisa S.; Silva, Nayane dos S. B.; Veiga‐Castelli, Luciana C.; Oliveira, Maria Luiza G.; Sadissou, Ibrahim Abiodoun; Massaro, Juliana Doblas; et al.
Abstract : Human leukocyte antigen‐C (HLA‐C) is a classical HLA class I molecule that binds and presents peptides to cytotoxic T lymphocytes in the cell surface. HLA‐C has a dual function because it also interacts with Killer‐cell immunoglobulin‐like receptors (KIR) receptors expressed in natural killer and T cells, modulating their activity. The structure and diversity of the HLA‐C regulatory regions, as well as the relationship among variants along the HLA‐C locus, are poorly addressed, and few population‐based studies explored the HLA‐C variability in the entire gene in different population samples. Here we present a molecular and bioinformatics method to evaluate the entire HLA‐C diversity, including regulatory sequences. Then, we applied this method to survey the HLA‐C diversity in two population samples with different demographic histories, one highly admixed from Brazil with major European contribution, and one from Benin with major African contribution. The HLA‐C promoter and 3′UTR were very polymorphic with the presence of few, but highly divergent haplotypes. These segments also present conserved sequences that are shared among different primate species. Nucleotide diversity was higher in other segments rather than exons 2 and 3, particularly around exon 5 and the second half of the 3′UTR region. We detected evidence of balancing selection on the entire HLA‐C locus and positive selection in the HLA‐C leader peptide, for both populations. HLA‐C motifs previously associated with KIR interaction and expression regulation are similar between both populations. Each allele group is associated with specific regulatory sequences, reflecting the high linkage disequilibrium along the entire HLA‐C locus in both populations.